Interstícios da saúde e território: trilhando percursos - Amaral, Henrique Melo Alves do (2019)
Building territory health set deep network relations involving political, institutional and community issues. This dissertation proposes to research the formations of territory on the health departing from its relational characteristics. We conducted our research following the meanings produced on territorialized health and social exchanges involved in this process. With this paper we invite to get implicated and to problematize the production of caring on the health analyzing the lived environment using as a parameter the relations between territorialities, community and individuals. For reaching this goal, we might discuss theoretical aspects of the social space and territorial dynamics besides approaching the health subject analyzing its integration and collectivized aspects departing from practical and lived components.